2022
DOI: 10.1021/acs.jmedchem.1c01296
|View full text |Cite
|
Sign up to set email alerts
|

Novel Selective Galectin-3 Antagonists Are Cytotoxic to Acute Lymphoblastic Leukemia

Abstract: Galectin-3 is a β-galactoside-specific, carbohydrate-recognizing protein (lectin) that is strongly implicated in cancer development, metastasis, and drug resistance. Galectin-3 promotes migration and ability to withstand drug treatment of B-cell precursor acute lymphoblastic leukemia (BCP-ALL) cells. Due to high amino acid conservation among galectins and the shallow nature of their glycan-binding site, the design of selective potent antagonists targeting galectin-3 is challenging. Herein, we report the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…All four inhibitors bind by anchoring their β-galactoside part (referred to as Gly-1; see Table ) at subsite C, forming hydrogen-bond interactions with side-chain atoms of His158, Asn160, Arg162, Asn174, and Glu184 and stacking interactions with the side chain of Trp181. This structural mode of binding of the Gly-1 ring to galectin-3 is very similar to the binding of the galactose ring of lactose, TDG, and most disaccharide ligands to galectin-3. , The second sugar ring (referred to as Gly-2; Table ) of all four inhibitors, binds partly at subsite D, with 13 , 14 , 15 , and 17 adopting similar conformations. The dihedrals of the thioglycosidic linkage, O5–C1–C2′–C3′, O5–C1–C2′–C1′, C2–C1–C2′–C3′, and C2–C1–C2′–C1′, have values between 57 to 64°, −133 to −142°, −56 to 66°, and 97 to 105°, respectively.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…All four inhibitors bind by anchoring their β-galactoside part (referred to as Gly-1; see Table ) at subsite C, forming hydrogen-bond interactions with side-chain atoms of His158, Asn160, Arg162, Asn174, and Glu184 and stacking interactions with the side chain of Trp181. This structural mode of binding of the Gly-1 ring to galectin-3 is very similar to the binding of the galactose ring of lactose, TDG, and most disaccharide ligands to galectin-3. , The second sugar ring (referred to as Gly-2; Table ) of all four inhibitors, binds partly at subsite D, with 13 , 14 , 15 , and 17 adopting similar conformations. The dihedrals of the thioglycosidic linkage, O5–C1–C2′–C3′, O5–C1–C2′–C1′, C2–C1–C2′–C3′, and C2–C1–C2′–C1′, have values between 57 to 64°, −133 to −142°, −56 to 66°, and 97 to 105°, respectively.…”
Section: Resultsmentioning
confidence: 73%
“…The structural elements that lead to the higher potency of the four studied inhibitors than that of lactose and TDG might be attributed to van der Waals contacts in subsite D. However, the rather large enthalpy gain might be due to additional factors, such as solvation differences and water-mediated hydrogen bonding, which can lead to enthalpy gains together with compensating entropy penalties. Thus, lactose and TDG form 5 hydrogen-bond interactions with water molecules when bound to galectin-3 , while 13 , 14 , 15 , and 17 form 9, 9, 8, and 7, respectively (Table ). It should be noted that 13 forms more hydrogen bonds than 14 but less van der Waals interactions, and yet 13 exhibits a weaker affinity.…”
Section: Resultsmentioning
confidence: 99%
“…The acylsulfonyl amide segment constructed charge–charge interactions and hydrogen binding interactions with Arg144 and Arg162, and these interactions directed the arylsulfonamide extending into a somewhat shallow but unique subpocket to gal-3. It was suggested that this area could be utilized to discover new inhibitors with gal-3 selectivity …”
Section: Results and Discussionmentioning
confidence: 99%
“…As a result, the 4-aryl-1,2,3-triazole thiodigalactoside derivative TD139 (also known as GB0139) was successfully developed and is currently in a phase IIb clinical study as an inhaled treatment for idiopathic pulmonary fibrosis (IPF) . Due to the high polarity and limited oral bioavailability of the disaccharides, the investigation focus was turned to the development of monogalactose-based derivatives, and a highly selective, orally available monosaccharide gal-3 inhibitor GB1211 was discovered, and it is now in a phase IIa clinical trial for the treatment of liver fibrosis and cancer …”
mentioning
confidence: 99%
“…The first described galectin inhibitors are molecules capable of binding to the CRD and preventing further ligand binding. Galectin inhibitors based on these competitive interactions consist of chemically modified mono or disaccharides structured around galactose ( 58 , 122 125 ), lactose ( 58 , 125 127 ), thiodigalactose (TDG) ( 34 , 128 132 ), talose ( 133 , 134 ) and lactulose ( 135 ). One of the first tempts to use this type of inhibitor in cancer consisted of administering a β-D-lactosyl-steroid.…”
Section: Current Galectin Inhibitorsmentioning
confidence: 99%